Studi Kinetika Kimia Pada Reaksi Saponifikasi Etil Asetat Dengan Metode Titrasi dan Konduktometri: Chemical Kinetic Study on Saponification Reaction of Ethyl Acetate Using Titration and Conductometric Methods - Pasaribu, Marvin Horale (Jurnal Jejaring Matematika dan Sains, 2022)
A chemical kinetics study on the saponification reaction of ethyl acetate by comparison of titration and conductometry methods has been conducted. First, though, this study started by reacting ethyl acetate with NaOH with a volume ratio of 2: 3 and was kept at a constant temperature of 35oC. The process of determining the order and rate constant of saponification reaction of ethyl acetate by hydroxide ions was carried out by comparing the analysis results with titration and conductometry methods with time variations of 5, 10, 15, 25, 40, and 60 minutes. The study's results proved that the saponification reaction follows the kinetics of the 2nd order reaction. It is supported by the analysis results using both analysis methods at time variations and obtaining a linear line graph with a positive gradient and an R2 value of 0.9757 and 0.9955, respectively, where both values are close to 1. Based on the titration method, the reaction rate (k) rated ethyl acetate saponification obtained a yield of 3.2375 M-1.min-1, while by the conductometry method, the rated value of the reaction rate obtained was 13.1973 M-1.min-1.